Control and orientation of urbanization of cities in developing countries: a case study of Kinshasa, Democratic Republic of the Congo - Innocent Mufungizi; Aymar Akilimali (Urban, Planning and Transport Research)
Urbanization is key to the development of a city. It is part of the Sustainable Development Goals. Developing countries are called upon to modernize and build urban infrastructure. There are several problems in developing countries: undirected and uncontrolled urbanization. This has several consequences, including the proliferation of slums, uncontrolled construction, erosion, flooding, and an increase in the crime rate. It is possible to combat these consequences and mitigate their effects by implementing solid urban planning that takes into account subdivision plans, the reinforcement of embankments, the expansion of the urban area, the construction of infrastructure, and their diversification.